The Creation of Cybrids Harboring Mitochondrial Haplogroups in the Taiwanese Population of Ethnic Chinese Background: An Extensive In Vitro Tool for the Study of Mitochondrial Genomic Variations. (6th December 2012) - Lin, Tsu-Kung; Lin, Hung-Yu; Chen, Shang-Der; Chuang, Yao-Chung; Chuang, Jiin-Haur; Wang, Pei-Wen; Huang, Sheng-Teng; Tiao, Mao-Meng; Chen, Jin-Bor; Liou, Chia-Wei
Abstract : Mitochondrial DNA (mtDNA) haplogroups may contribute to the development of aging-related diseases. A reliable in vitro cellular system for investigating the physiologic significance of mtDNA haplogroups is essential. This study aims to construct and characterize a series of cybrid cell lines harboring variant mtDNA haplogroups collected from healthy Taiwanese volunteers. Cybrid cells harboring different mtDNA haplogroups like B4a, B4b, B4c, B4d, B5, R, F1a, F2, D4e, D4a, D5b, D5a, E, M8, C, and N9a were prepared. Luminex 1000 and full-length mtDNA sequencing were used to confirm that mtDNA haplogroups of transmitochondrial cybrids were identical to their original donors. Cybrid B4b had a significantly lower oxygen consumption rate and higher mitochondrial membrane potential compared to F1a, B5, D5a, D4a, and N9a but had more susceptibility to H2 O2 -induced oxidative stress than cybrid F1a, D4a, and N9a. Cybrid N9a had better oxygen consumption and H2 O2 -challenged viability compared to B4b, F1a, B5, D5a, and D4a. A series of cybrid cells harboring the main haplogroups of the Taiwanese population with ethnic Chinese background has been developed in vitro . With this mtDNA haplogroup population, the underlying mechanisms of aging-related diseases may be better understood, and therapeutic interventions can be accelerated.